Physical Quality of Banana Stem and Indigofera sp Mixture Fermented Using MA-11 at Different Doses - Amanda Istiana; Sri Sukaryani (Jurnal Biologi Tropis, 2026)
This study aimed to evaluate the effect of different doses of MA-11 on the physical quality, pH, and dry weight of a fermented mixture of banana pseudostem and Indigofera forage with molasses addition. Fermentation was applied as a method to improve the utilization of local feed resources with low physical quality. The experiment was conducted using a Completely Randomized Design with three treatments and four replications. The treatments consisted of P0: banana pseudostem + Indigofera forage + molasses (control), P1: banana pseudostem + Indigofera forage + molasses + 1 cc MA-11, and P2: banana pseudostem + Indigofera forage + molasses + 2 cc MA-11. Fermentation was carried out for 12 days. The observed variables included physical quality (color, aroma, and texture), pH value, and dry weight. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test. The results showed that MA-11 supplementation significantly improved the physical quality of the fermented mixture, as indicated by higher scores for color, aroma, and texture compared to the control. In addition, MA-11 significantly reduced the pH value of the fermented product. However, the application of MA-11 had no significant effect on dry weight. It can be concluded that the fermentation of banana pseudostem and Indigofera forage using MA-11 effectively improved physical quality and fermentation characteristics, although it did not affect dry weight.